2018
DOI: 10.3390/rs10091481
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Permafrost Coasts of Baydaratskaya Bay (Kara Sea) Based on Multi-Temporal Remote Sensing Data

Abstract: Arctic coasts that are composed of frozen deposits are extremely sensitive to climate change and human impact. They retreat with average rates of 1–2 m per year, depending on climatic and permafrost conditions. In recent decades, retreat rates have shown a tendency to increase. In this paper, we studied the coastal dynamics of two key sites (Ural and Yamal coasts) of Baydaratskaya Bay, Kara Sea, where a gas pipeline had been constructed. Based on multi-temporal aerial and satellite imagery, we identified coast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(46 citation statements)
references
References 44 publications
2
43
1
Order By: Relevance
“…At the Marresale site (Figure ), the cliff retreated at mean annual rates of 0.5–2.5 m/yr between 1978 and 2010, with a maximum rate of 3.3 m/yr in 1989 and 1990 . By contrast, the south‐east coast of Baydaratskaya Bay in the south‐west Yamal Peninsula was eroding at mean annual rates of 0.1–0.6 m/yr, which were lower than those reported in the central–west and north‐west Yamal Peninsula coasts. Most coastal sites in the western Baydaratskaya Bay and the western Yugorsky Peninsula were retreating at mean annual rates of 0.4–2.0 m/yr, although several of the sites were stable during 2005 and 2012 .…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…At the Marresale site (Figure ), the cliff retreated at mean annual rates of 0.5–2.5 m/yr between 1978 and 2010, with a maximum rate of 3.3 m/yr in 1989 and 1990 . By contrast, the south‐east coast of Baydaratskaya Bay in the south‐west Yamal Peninsula was eroding at mean annual rates of 0.1–0.6 m/yr, which were lower than those reported in the central–west and north‐west Yamal Peninsula coasts. Most coastal sites in the western Baydaratskaya Bay and the western Yugorsky Peninsula were retreating at mean annual rates of 0.4–2.0 m/yr, although several of the sites were stable during 2005 and 2012 .…”
Section: Discussionmentioning
confidence: 76%
“…Numerous studies have looked at the coastal dynamics in the Kara Sea coasts since the 1960s based on field measurements and analyses of satellite and aerial images (e.g., ). They revealed that mean annual rates of coastal retreat ranged between 0.2 m/yr and 2.0 m/yr for most of the Kara Sea coasts in the last 50 years while several coastal sites were stable or accreting.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…200 mm a −1 (Burn, 2012). The average coastal erosion rate for the whole of Qikiqtaruk -Herschel Island was 0.45 m a −1 between 1970 and 2000 (Lantuit and Pollard, 2005;Obu et al, 2015) and 0.68 m a −1 between 2000 and 2011 (Obu et al, 2016).…”
Section: Study Sitementioning
confidence: 94%